Reactivity of towards copper (I) compounds: Synthesis of binuclear heteromettalic species having CS2 bridging Fe(O) and Cu(I) - Muraoka, T. K. [UNESP]; Duarte, A. P. [UNESP]; Takahashi, P. M. [UNESP]; Nogueira, V. M. [UNESP]; Netto, A. V.G. [UNESP]; Mauro, A. E. [UNESP] (My University, 2007)
This work describes the one pot syntheses and characterization of two new heterometallic carbonyl compounds of the type [Fe(CO)3(m-CS2)(PPh3)(CuX)], X = Cl, ClO4. Both compounds were investigated by infrared and 31P{1H} NMR spectroscopies in order to clarify the coordination mode of the carbonyl groups, as well the bridging disposition of the carbon disulfide between iron (0) and copper (I) atoms.
Reatividade do [Fe(CO)2(2-CS2)(PPh3)2] frente a compostos de Cu(I): Síntese de espécies binucleares heterometálicas contendo CS2 em ponte entre Fe(0) e Cu(I).
Keywords: Carbon disulfide; Copper (I); Heterometallic carbonyl complexes; Iron (0)